Wide-Ranging Temporal Variation in Transoceanic Movement and Population Mixing of Bluefin Tuna in the North Atlantic Ocean - Rooker, Jay R.; Fraile, Igaratza; Liu, Hui; Abid, Noureddine; Dance, Michael A.; Itoh, Tomoyuki; Kimoto, Ai; Tsukahara, Yohei; Rodriguez-Marin, Enrique; Arrizabalaga, Haritz (Frontiers in Marine Science, 2019)
Uncertainty regarding the movement and population exchange of Atlantic bluefin tuna (Thunnus thynnus) from the two primary spawning areas (Gulf of Mexico, Mediterranean Sea) is increasingly implicated as a major impediment for the conservation of this species. Here, two mixture methods were applied to natural chemical markers (18O and 13C) in otoliths (ear stones) to comprehensively investigate the nature and degree of transoceanic movement and mixing of eastern and western populations in several areas of the North Atlantic Ocean that potentially represent mixing hotspots. Areas investigated occurred on both sides of the 45W management boundary as well as waters off the coast of Africa (Morocco, Canary Islands) where both populations are known to occur. Projections of population composition (i.e., natal or nursery origin) from a multinomial logistic regression (MLR) classification method with different probability thresholds were generally in agreement with maximum likelihood estimates from the commonly used mixed-population program HISEA; however, predicted contributions for the less abundant population were occasionally higher for MLR estimates. Both MLR and HISEA clearly showed that mixing of Atlantic bluefin tuna in the Central North Atlantic Ocean was highly variable from year to year with expatriates of eastern or western origin commonly crossing into the other management area. Pronounced transoceanic movement and mixing of western migrants was also present off the coast of Africa, with the occurrence of western migrants in the Canary Islands and Morocco ranging from zero to the majority of the individuals assayed for the years examined. Results indicate highly variable rates of movement and population exchange for Atlantic bluefin tuna, highlighting the need for temporally resolved estimates of natal origin in mixing hotspots to improve population models used to evaluate the status of this threatened species.